NEEDS AND EVALUATION OF BEAUTY CARE AMONG VIETNAMESE WOMEN (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current situation and assess the demand for beauty care among Vietnamese women.Subjects and methods: A cross-sectional descriptive study was conducted on 258 Vietnamese women, using an online survey in April 2022.Results: The study population mainly consisted of young women (aged 20-29 years, 69%), with the highest demand for skincare (95%), physical exercise (70.2%), and adequate sleep (65.5%). Most participants began to take an interest in beauty care at the age of 18-29 (62.4%), with the lowest proportion in those over 40 years old (3.5%). The majority reported that beauty care enhances self-confidence (95%). The main barriers affecting demand were financial constraints (68.9%) and lack of time (52.3%).Conclusion: The beauty care needs of most young women today are focused on skincare and a healthy lifestyle (exercise, sufficient sleep, eating organic food...); women typically begin to care about beauty between the ages of 18 and 29 and appreciate the role of beauty care in boosting self-confidence, but are still limited by time and finances.
Keywords: Beauty care, Vietnamese women, demand.